Using Pictures to Enhance Descriptive Text Writing Skills for Ninth Grade Students at Smpk Muder Teresa Kupang in the School Year 2023/2024. - Rozita Y. Lodo; Chamelya Vivi Crystanty Sene; Mansuetus Mola (Journal Emerging Technologies in Education, 2024)
This study aims to determine whether there is a significant impact from using pictures in descriptive writing instruction for ninth grade students at SMPK Muder Teresa Kupang in the academic year 2023–2024. This pre-experimental research used a pre-test-treatment-post-test design. It uses 2 pre-test-post-test cycles and uses tests as instruments. This research involved five students in class IX at SMPK Muder Teresa Kupang. Research data was collected by giving students written descriptive text tests before and after the test. According to data analysis, According to this study, the pre- and post-test results differed significantly. This demonstrates how teaching writing to students through picture techniques can improve their writing, particularly when it comes to descriptive writing.